2012
DOI: 10.4161/onci.1.1.18312
|View full text |Cite
|
Sign up to set email alerts
|

NK cells sense tumors, course of disease and treatments

Abstract: The recent findings on NK activation indicate that these cells are important antitumor effectors. NK cells participate in the graft-vs.-leukemia effect to control the relapse in leukemic patients transplanted with allogeneic hematopoietic stem cells. In various tumors, correlation between NK cell infiltrates and prognosis were reported. However, tumor-infiltrating NK cells are yet poorly characterized. We here summarize our results and the recent studies of the literature on tumor-infiltrating NK cells, and di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
50
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(51 citation statements)
references
References 75 publications
0
50
1
Order By: Relevance
“…Romagnani and colleagues previously showed that lymph node could be the site of NK cell final maturation during the course of an immune reaction and resident CD56 bright NK cells from paracortical/ follicular hyperplasic lymph node may acquire CD16 and KIR and recirculate in the blood (31). It is interesting to note that our data indicate different regulation of NK receptors in CD16 but that NKp46 was correlated with NKG2D (21,23,32 Immunotherapy may be considered as a complementary approach that can be integrated in therapeutic strategies at different stages of the disease. In patients with metastatic melanoma, blocking immune checkpoint of T-cell activation with specific mAbs (anti-CTLA4 and anti-PD1) is a promising issue to restore efficient antitumor immune response.…”
Section: Discussioncontrasting
confidence: 45%
“…Romagnani and colleagues previously showed that lymph node could be the site of NK cell final maturation during the course of an immune reaction and resident CD56 bright NK cells from paracortical/ follicular hyperplasic lymph node may acquire CD16 and KIR and recirculate in the blood (31). It is interesting to note that our data indicate different regulation of NK receptors in CD16 but that NKp46 was correlated with NKG2D (21,23,32 Immunotherapy may be considered as a complementary approach that can be integrated in therapeutic strategies at different stages of the disease. In patients with metastatic melanoma, blocking immune checkpoint of T-cell activation with specific mAbs (anti-CTLA4 and anti-PD1) is a promising issue to restore efficient antitumor immune response.…”
Section: Discussioncontrasting
confidence: 45%
“…Compared with blood NK cells, only a limited amount of information is available on tissue infiltrating NK-TILs in breast cancer (Jochems and Schlom, 2011), which usually present more severe phenotypic and functional alterations compared with circulating or non-cancerous tissue-infiltrating NK counterparts (Fregni et al, 2012). Although the number of NK cells coming into contact with neoplastic cells constitute a small percentage of the infiltrating lymphocytes, they can play an important role in the prognosis of tumors (Stojanovic and Cerwenka, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Correlation between NK cell infiltrates and prognosis has been reported in various tumors. However, tumor-infiltrating NK cells are yet poorly characterized (Fregni et al, 2012). Mamessier et al (2011) have shown that breast tumor progression involves NK cell dysfunction and that breast tumors mold their environment to evade NK cell anti-tumor immunity.…”
Section: Introductionmentioning
confidence: 99%
“…15 In addition, chemotherapy treated patients displayed distinct phenotypic modulations, 24 indicating that tumor progression and conventional chemotherapy may interfere with NK cell status in melanoma patients. 25 In a recent study, comparing tumor positive and tumor-free Sentinel lymph nodes (SLN), we found that more numerous cytotoxic cells (CD8 C cells, Granzyme C cells, NK cells) infiltrated tumor-free SLN. We also found that NK cells in SLN correlated with higher rate of relapses, supporting a tumor-promoting role of NK cells in SLN.…”
Section: Discussionmentioning
confidence: 99%